(untitled) (Información, cultura y sociedad, 2014)
The article analyzes some of the developments and trends on library and information center management from the 60’s to the present, along with the factors that influenced them, such as the social, political, economic and technological environment, and the managerial theories and practices applied by the for-profit and non-profit organizations. It analyzes the main managerial concepts and practices in the library field during these years, its successes, obstacles and failures, and the major past and present trends.